Elements of Architecture? Rem Koolhaas. - Koolhaas, Rem; Avermaete, Tom, 1971-; Clouette, Benedict; Easterling, Keller; Jiren, Feng; Maak, Niklas; Marot, Sébastien; Mcleod, Kevin; Zaero Polo, Alejandro; Zhenning, Fang; c-lab/Jeffrey Inaba (Keulen : taschen, 2018)
AMO/ Harvard Graduate School of Design ; Trüby, Stephan ; Westcott, James ; Petermann, Stephan ; Boom, Irma
boekontwerp Irma Boom
Fundamentals, Architectuur Biennale van Venetië, La Biennale di Venezia, 2014
boek
Keywords: Koolhaas, Rem